Employee behavior among expatriates in Scope International (M) Sdn Bhd / Muhammad Aswad Md Nor - Md Nor, Muhammad Aswad (Faculty of Business and Management, 2010)
Scope International is the Standard Chartered Group’s Global Technology & Operations Hub. A wholly owned subsidiary of Standard Chartered Bank, United Kingdom, Scope International is the first Global Shared Services Centre of an international bank in Malaysia. Established in 2001, Scope International provides a wide range of services to the Standard Chartered Bank in more than 70 countries worldwide. They comprise software and systems development, wholesale and consumer banking operations, contact centre, I.T. and Helpdesk services. Scope’s software division, International Software Centre Malaysia (ISCM) houses the largest software development centre and largest software testing facility in Malaysia. Scope International Malaysia currently employs more than 3,000 employees. With such a large number of employees, there surely is a variety of behavior among employees especially from expatriates from India and Singapore. But as a reputable company, Scope International Malaysia must distinguish themselves over other bank regardless of international bank or local bank in term of behavior of their employees. The research conducted is made to find whether the employees from India and Singapore have the behavior that the company wanted that is the Supportive, Smart, Courageous, Passionate and Reliable (S2CPR) behavior. This behavior will determine whether Scope International Malaysia has distinguished themselves among their competitor in the banking industry in Malaysia.